Disrupted function of lactate transporter MCT1, but not MCT4, in Schwann cells affects the maintenance of motor end‐plate innervation. Issue 1 (20th July 2020) - Bouçanova, Filipa; Pollmeier, Gill; Sandor, Katalin; Morado Urbina, Carlos; Nijssen, Jik; Médard, Jean‐Jacques; Bartesaghi, Luca; Pellerin, Luc; Svensson, Camilla I; Hedlund, Eva; Chrast, Roman
Abstract: Recent studies in neuron‐glial metabolic coupling have shown that, in the CNS, astrocytes and oligodendrocytes support neurons with energy‐rich lactate/pyruvate via monocarboxylate transporters (MCTs). The presence of such transporters in the PNS, in both Schwann cells and neurons, has prompted us to question if a similar interaction may be present. Here we describe the generation and characterization of conditional knockout mouse models where MCT1 or MCT4 is specifically deleted in Schwann cells (named MCT1 and MCT4 cKO). We show that MCT1 cKO and MCT4 cKO mice develop normally and that myelin in the PNS is preserved. However, MCT1 expressed by Schwann cells is necessary for long‐term maintenance of motor end‐plate integrity as revealed by disrupted neuromuscular innervation in mutant mice, while MCT4 appears largely dispensable for the support of motor neurons. Concomitant to detected structural alterations, lumbar motor neurons from MCT1 cKO mice show transcriptional changes affecting cytoskeletal components, transcriptional regulators, and mitochondria related transcripts, among others. Together, our data indicate that MCT1 plays a role in Schwann cell‐mediated maintenance of motor end‐plate innervation thus providing further insight into the emerging picture of the biology of the axon‐glia metabolic crosstalk. Main Points: MCT1 expressed by Schwann cells is necessary for the long‐term motor end‐plate innervation in the PNS. Schwann cell‐specific loss of MCT4 does not lead to detectable changes in the PNS. Absence of MCT1 in Schwann cells leads to transcriptional changes in spinal cord motor neurons.